2021
DOI: 10.1103/physrevb.103.054439
|View full text |Cite
|
Sign up to set email alerts
|

Confined magnetoelastic waves in thin waveguides

Abstract: The characteristics of confined magnetoelastic waves in nanoscale ferromagnetic magnetostrictive waveguides have been investigated by a combination of analytical and numerical calculations. The presence of both magnetostriction and inverse magnetostriction leads to the coupling between confined spin waves and elastic Lamb waves. Numerical simulations of the coupled system have been used to extract the dispersion relations of the magnetoelastic waves as well as their mode profiles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…In fact, the dispersion relation of SW modes in a longitudinally magnetized stripe can be calculated analytically neglecting the quantization along the thickness direction [ 20 , 30 , 31 , 32 , 33 ], with the formula given by where is the gyromagnetic ratio, , the wave numbers , where d is the thickness of the wire, and . Note that , which is quantized and yields multiple branches of the dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the dispersion relation of SW modes in a longitudinally magnetized stripe can be calculated analytically neglecting the quantization along the thickness direction [ 20 , 30 , 31 , 32 , 33 ], with the formula given by where is the gyromagnetic ratio, , the wave numbers , where d is the thickness of the wire, and . Note that , which is quantized and yields multiple branches of the dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated in Ref. 71 that the extension can be used to simulate confined magneto-elastic waves in thin waveguides. It would be nice to briefly mention here if there are other geometries where their extension can (or cannot) be used.…”
Section: Discussionmentioning
confidence: 99%
“…Below, we reproduce verbatim the input script (including annotations) used to generate the data in Figure 7 in Ref. 71 as an example. As output, the input script generates data in the .ovf format.…”
Section: Use Casesmentioning
confidence: 99%
“…In the latter case, the elastic medium should form a thin film or a waveguide grown on a low-impedance substrate (see, e.g., ref. [34]) to guarantee that a sufficient fraction of the elastic wave energy propagates in a SAFM (in the case of surface acoustic waves it is achieved naturally by the wave localization). Of course, the optimal operation conditions for different elastic wave modes (for instance, the angle φ between the wave propagation direction and SAFM magnetization) will be different.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%